Enhanced Software Development Effort and Cost Estimation Using Fuzzy Logic Model - Su, Moon Ting; Ling, Teck Chaw; Phang, Keat Keong; Liew, Chee Sun; Man, Peck Yen (Malaysian Journal of Computer Science, 2007)
The development of software has always been characterized by parameters that possess certain level of fuzziness. This requires that some degree of uncertainty be introduced in the models, in order to make the models realistic. Fuzzy logic fares well in this area. Many of the problems of the existing effort estimation models can be solved by incorporating fuzzy logic. Besides, fuzzy logic had been combined with algorithmic, non-algorithmic effort estimation models as well as a combination of them to deal with the inherent uncertainty issues. This paper also described an enhanced fuzzy logic model for the estimation of software development effort. The model (FLECE) possesses similar capabilities as the previous fuzzy logic model. In addition to that, the enhancements done in FLECE improved the empirical accuracy of the previous model in terms of MMRE (Mean Magnitude of Relative Error) and threshold-oriented prediction measure or prediction quality (pred).